Performance Improvement of Multilevel Load Power System by Using Two-Stage s Fuzzy Controller (University of Thi-Qar Journal for Engineering Sciences, 2011)
This paper presents a new approach to improve the performance of power system by enhancing the voltage profile and reducing the real power losses based on two stages fuzzy controller which is used to select the appropriate size and location of capacitor banks required to minimize the power losses and maintain the voltage profile in permissible limits.The first stage of fuzzy controller is used to specify the optimal location of capacitors installation, while the optimal size is specified by the second stage . The proposed method is tested on a 34-bus, 74-transmission lines from Iraqi Northern power system with multilevel ofloads. The load levels are represented by 50%, 75%, 100% and 125% of peak load and satisfied results are obtained to show the feasibility and flexibility of the proposed method.